THE SODIUM CHLORIDE MINERAL WATERS IN MUREŞ COUNTY, LASTING TOURISM PROTECTION AND CAPITALIZATION - CIANGĂ N.; COSTEA D. (Aerul şi Apa: Componente ale Mediului, 2014)
This study represents a continuation of the research and assessment of sodium chloride mineral water resources on the territory of the Transylvanian Depression, especially regarding the emergence of salt springs, which are still not to be found in the scholarly literature. Therefore, Mureş County will be analysed this time, a county where certain researches have been done before. Field research can be also added to these, representing the only possibility to update the data regarding the existent salt springs. The first examples already known are the sodium chloride mineral waters billeted in the lakes located in Sovata and Jabeniţa. Locations with sodium chloride mineral waters which appear at the surface under the form of salt springs with a salinity exceeding 1 g/l, as compared to the ones specified, are Sărmăşel, Târnăveni, Sângeorgiu de Mureş, Gurghiu, Orşova, Brâncoveneşti, Lunca Mureşului, Ibăneşti and Ideciu de Jos. As far as the protection of these resources is concerned, the main debated problems are related to phenomena such as their clogging and desalination, which causes many sodium chloride mineral water springs to become ephemeral.